DAPK1 Promoter Methylation and Cervical Cancer Risk: A Systematic Review and a Meta-Analysis. - Antonella Agodi; Martina Barchitta; Annalisa Quattrocchi; Andrea Maugeri; Manlio Vinciguerra (PLoS ONE)
Objective The Death-Associated Protein Kinase 1 (DAPK1) gene has been frequently investigated in cervical cancer (CC). The aim of the present study was to carry out a systematic review and a meta-analysis in order to evaluate DAPK1 promoter methylation as an epigenetic marker for CC risk. Methods A systematic literature search was carried out. The Cochrane software package Review Manager 5.2 was used. The fixed-effects or random-effects models, according to heterogeneity across studies, were used to calculate odds ratios (ORs) and 95% Confidence Intervals (CIs). Furthermore, subgroup analyses were conducted by histological type, assays used to evaluate DAPK1 promoter methylation, and control sample source. Results A total of 20 papers, published between 2001 and 2014, on 1929 samples, were included in the meta-analysis. DAPK1 promoter methylation was associated with an increased CC risk based on the random effects model (OR: 21.20; 95%CI = 11.14-40.35). Omitting the most heterogeneous study, the between study heterogeneity decreased and the association increased (OR: 24.13; 95% CI = 15.83-36.78). The association was also confirmed in all the subgroups analyses. Conclusions A significant strong association between DAPK1 promoter methylation and CC was shown and confirmed independently by histological tumor type, method used to evaluate methylation and source of control samples. Methylation markers may have value in early detection of CC precursor lesions, provide added reassurances of safety for women who are candidates for less frequent screens, and predict outcomes of women infected with human papilloma virus.